Strategies of translating Culture-Specific Items (CSIs) in Mo Yan’s Red Sorghum - Zuo, Yunchao; Syed Abdullah, Syed Nurulakla; Toh, Florence Haw Ching (International Islamic University Malaysia, 2025)
This study focused on the translation of culture-specific items (CSIs) in Mo Yan’s novel Red Sorghum and the applicability of Functionalist Theory in analysing the data. This aim was divided into three specific objectives: identifying the strategies of translating CSIs, exploring their occurrence rates, and examining whether or not functionalist theory is applicable to the analysis of data. Drawing upon Aixelá’s translation strategies and Nida’s classification, this study examined translation strategies within the framework of functionalist theory. The results showed that the most commonly used techniques are absolute universalisation and linguistic translation. Second, different translation procedures are required for different classifications of CSIs. Thirdly, the study found that in order to maintain artistic and aesthetic value, an aesthetic rule shall be considered in literary translation.